Derivational Suffixes In The Novel A Little Princess - Pramesti, Ni Kadek Pramudhea Ayu; Aryani, I Gusti Agung Istri; Indrawati, Ni Luh Ketut Mas (Denpasar Institute, 2025)
This research focuses on the use of derivational suffixes in A Little Princess by Frances Hodgson Burnett. The study aims to identify the types of derivational suffixes and to explain how they influence class-changing transformations in the novel. Data were collected through documentation and systematic note-taking, and analyzed using a descriptive qualitative method grounded in Plag’s (2003) and Bauer’s (1983) morphological theories. The analysis identified a total of 161 derivational suffixes, consisting of four types: nominal, verbal, adjectival, and adverbial suffixes. Among these, the adverbial suffix -ly was the most frequent, occurring 64 times, and primarily functioning to modify actions or states by expressing manner or attitude. The findings further reveal two derivational effects: class-maintaining and class-changing derivation. Class-changing derivations are dominant, with 158 instances, while class-maintaining derivations occur in only 3 instances. These results underscore the significance of derivational morphology in literary texts, demonstrating how suffixation contributes to lexical expansion and syntactic variation, and offering insights into how morphological processes shape meaning and stylistic expression in literary analysis.